1990
DOI: 10.1111/j.1745-4530.1990.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

LIQUID‐TO‐PARTICLE HEAT TRANSFER DURING CONTINUOUS TUBE FLOW: INFLUENCE of FLOW RATE and PARTICLE to TUBE DIAMETER RATIO1

Abstract: Liquid‐to‐particle convective heat transfer coefficients were measured during continuous flow through tubes, using an experimental technique in which a thermocouple was moved at the same speed as the particle. Water was used as the carrier fluid and transducer particles were made hollow to approximate densities of real food particles. Results from over 250 experimental runs over a fluid Reynolds number range from 7300 to 43600, showed that the convective coefficient was increased significantly with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 10 publications
2
17
1
Order By: Relevance
“…More recent work from this laboratory (Balasubramaniam and Sastry 1994) has found that under laminar flow conditions, the effect of particle-to-pipe dimension ratio was not clear cut; this was attributed to variation in particle trajectories (which were not controlled). Zitoun and Sastry (1994) determined convective heat transfer coefficients for cubic particles in non-Newtonian carrier fluids in laminar flow using the moving thermocouple approach of Sastry et al (1990). Results indicated increasing heat transfer coefficients with increasing flow rate, decreasing viscosity and decreasing particle-to-tube dimension ratio.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work from this laboratory (Balasubramaniam and Sastry 1994) has found that under laminar flow conditions, the effect of particle-to-pipe dimension ratio was not clear cut; this was attributed to variation in particle trajectories (which were not controlled). Zitoun and Sastry (1994) determined convective heat transfer coefficients for cubic particles in non-Newtonian carrier fluids in laminar flow using the moving thermocouple approach of Sastry et al (1990). Results indicated increasing heat transfer coefficients with increasing flow rate, decreasing viscosity and decreasing particle-to-tube dimension ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Since time has a large error coefficient value, longer residence times are desirable (although not practical). Other precautions and sources of experimental error are described by Sastry et al (1990).…”
Section: Moving Thermocouple Methodsmentioning
confidence: 99%
“…The presumption of zero relative velocity, while conservative, is contradicted by most measurements of h fp under continuous flow conditions (Heppell, 1985;Sastry et al, 1989Sastry et al, , 1990Mwangi et al, 1993). Most such studies have indicated that h fp is significantly greater than expected from the zero relative velocity conjecture.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ultrasonic energy has successfully been exploited in the past two decades for medical diagnosis and industrial purposes (Chernikova, 1977;Floros & Liang, 1994;Gallego, 1998;Satstri, Lima, Brim, Brunn, & Heskitt, 1990). However, relatively lesser attention have been paid by agricultural scientists to its application in agriculture and food industry.…”
Section: Introductionmentioning
confidence: 98%